4-6x=-5x-3

Simple and best practice solution for 4-6x=-5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-6x=-5x-3 equation:


Simplifying
4 + -6x = -5x + -3

Reorder the terms:
4 + -6x = -3 + -5x

Solving
4 + -6x = -3 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
4 + -6x + 5x = -3 + -5x + 5x

Combine like terms: -6x + 5x = -1x
4 + -1x = -3 + -5x + 5x

Combine like terms: -5x + 5x = 0
4 + -1x = -3 + 0
4 + -1x = -3

Add '-4' to each side of the equation.
4 + -4 + -1x = -3 + -4

Combine like terms: 4 + -4 = 0
0 + -1x = -3 + -4
-1x = -3 + -4

Combine like terms: -3 + -4 = -7
-1x = -7

Divide each side by '-1'.
x = 7

Simplifying
x = 7

See similar equations:

| T^2-4=3t | | 2w^2-w^2-w-9=0 | | 35+17x=x+3 | | 8x+2=9x-10 | | ½-3x=6,5+½x | | 2w^2-5w-6-w^2+4w-3=0 | | 23x-22x+3-2x+4+128=0 | | 72x+4*7x-5=0 | | 4/x-3=5/x-2 | | 15x+22=5x+234 | | -1(x+5)(x-4)=0 | | 4x-(10x+26)=70 | | 4x-8y=7 | | 18+45+7x^2= | | 1/2(8-x)=6 | | -6n+21=12n+15 | | 5+A=3-X+Y | | 8(4+3)+2(7-5)/5(7-3)2 | | 100=9+8+14+x | | 3(a-5)= | | A=3-X+Y | | A=3+-1X+1Y | | (2x+7)+(-5x-14)= | | (6x+8)+(-7x-19)= | | 4x+5=87-2x | | 14xy-21yz= | | 4x+3y=30 | | 2y-7=y+9 | | (x+4)(x-1)=24 | | 2(x+5)-6=16 | | -15=x+(-16) | | X-Y+A=3 |

Equations solver categories